PRESEPSI PENGELOLA DAN IMPLEMENTASI KEPATUHAN SYARIAH PADA BMT BINAMAS - Anisa Nur Azizah; Sepky Mardian; Ahmad Baehaqi (IAIN Lhokseumawe, 2021)
This study aims to examine the understanding of managers' perceptions in interpreting Sharia compliance practices and to know Sharia compliance practices at BMT Binamas Purworejo. The methodology used is a qualitative phenomenological study approach with an interpretive paradigm. The research findings indicate that the respondents have been able to interpret the practice of Sharia compliance as an important element in the BMT with their respective perceptions. Furthermore, the implementation of Sharia compliance is measured by 10 focus research discussions contained in the Regulation of the Deputy for Supervision of the Ministry of Cooperatives and Small and Medium Enterprises No. 07 / PER / DEP.6 / IV / 2016 concerning Guidelines for Health Assessment of Cooperatives for Savings and Loans and Sharia Financing.